(untitled) (Shahroud Journal of Medical Sciences, 2024)
Pedestrians are 23% of the victims of road traffic crashes in Iran. The second cause of injuries in these accidents is also assigned to this group. The most important cause of this vulnerability is the behavior of pedestrians, Nevertheless the interventions to change behavior in solving this major problem have been the least effective. The cause of this lack of effectiveness is related to voluntary choice in behavior change, seen in all regions of the world. This brief report introduces the use of effective interventions to policymakers by explaining the role of public health in promoting the safety of pedestrians. Reducing the speed of vehicles in residential areas by implementing measures that will change speed control from a voluntary choice to a compulsory choice is a very effective strategy for improving the health and safety of pedestrians.